2014
DOI: 10.1016/s2213-2600(14)70157-2
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of nicotine patches in pregnancy on infant and maternal outcomes at 2 years: follow-up from the randomised, double-blind, placebo-controlled SNAP trial

Abstract: National Institute for Health Research Health Technology Assessment Programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 29 publications
1
63
0
Order By: Relevance
“…Possible beneficial effects were concluded for three trials (El-Mohandes et al 2013; Oncken et al 2008; Wisborg et al 2000) based on increases in birthweight and/or gestational age in the NRT group. The large SNAP trial (Cooper et al 2014b) also noted a beneficial effect on development at 2 years. Possible adverse effects were also noted, with the endpoints varying: overall congenital abnormalities (Morales-Suarez-Varela et al 2006); infantile colic (Milidou et al 2012); attention-deficit/hyperactivity disorder (Zhu et al 2014); low birthweight and preterm birth (Gaither et al 2009); respiratory system abnormalities (Dhalwani et al 2015); rapid fetal movements (Kapur et al 2001); and negative birth outcomes (Pollak et al 2007).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Possible beneficial effects were concluded for three trials (El-Mohandes et al 2013; Oncken et al 2008; Wisborg et al 2000) based on increases in birthweight and/or gestational age in the NRT group. The large SNAP trial (Cooper et al 2014b) also noted a beneficial effect on development at 2 years. Possible adverse effects were also noted, with the endpoints varying: overall congenital abnormalities (Morales-Suarez-Varela et al 2006); infantile colic (Milidou et al 2012); attention-deficit/hyperactivity disorder (Zhu et al 2014); low birthweight and preterm birth (Gaither et al 2009); respiratory system abnormalities (Dhalwani et al 2015); rapid fetal movements (Kapur et al 2001); and negative birth outcomes (Pollak et al 2007).…”
Section: Resultsmentioning
confidence: 97%
“…The longest was the 7½-year follow-up for cancer of participants in the Lung Health Study (Murray et al 2009) and the follow-up until 2011 for investigating attention-deficit/hyperactivity disorder (ADHD) of children born between 1996 and 2003 in the Danish National Birth Cohort study (Zhu et al 2014). A follow-up until 2006 for investigating strabismus in the same study (Torp-Pedersen et al 2010) and two-year follow-ups in two clinical trials (Cooper et al 2014b; Mohiuddin et al 2007) were the only other studies appearing to involve more than one year of follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a metaanalysis of these trials, smoking cessation rates late in pregnancy were not significantly improved with NRT (10.8%) compared to placebo (8.5%), RR:1.24 (CI 0.95-1.64) [49]. There is some evidence from smaller trials that NRT use is safe and can show benefit in development for up to 2 years [50][51]; however, additional trials are warranted to confirm these findings.…”
Section: Pregnancymentioning
confidence: 97%
“…Lastly, a recent Cochrane review suggests that use of medicinal nicotine by pregnant women who smoke has no negative effects on birth outcomes [57]. A randomized trial of use of nicotine during pregnancy showed that children born to smokers who used pharmaceutical nicotine products during pregnancy were more likely to have better developmental outcomes than children of smokers who received a placebo [58]. All of these findings support the premise that the adverse outcomes are most likely due to other toxicants carried in tobacco smoke, not to the nicotine.…”
Section: Effects Of Nicotine Inhalation By the E-cigarette Usermentioning
confidence: 99%